A responsabilidade civil e a gestão de riscos no agronegócio: os danos ambientais provocados por deriva pelo uso de agrotóxicos em propriedades adjacentes - Souza, Kamilla Prado (Universidade do Vale do Rio dos Sinos, 2022)
Agribusiness is a constantly growing sector, because Brazil is one of the largest producers of food in the world, and for this reason, the growth of planted areas increases rapidly. However, to meet the large demand, the use of agrochemicals has intensified in recent years, placing the country in the ranking of largest buyer of chemicals, and to improve the applicability of these products, the use of aerial and terrestrial sprayers began. However, the use of this equipment on farms has brought about issues that were not previously discussed, which is the civil responsibility of the agents involved, when due to the applicability of the product, transport to other areas-not targeted from the surrounding area-occurs, a factor known as drift, resulting in environmental damage. For this, the problem was proposed in the sense of how the agribusiness managers should plan the prevention of possible environmental damage caused by drift due to the applicability of pesticides in rural properties in order to prevent or reduce losses? In search of a possible answer to the problem, it was established as a hypothesis, the need for agribusiness managers to know the risks of their activity and promote risk management mechanisms to prevent damage, investing in equipment, developing guidelines and procedures that enable an option with low harmful impact to farmers. Regarding the general objective, the research sought to demonstrate the civil liability arising from the drift from the use of agrochemicals in agribusiness and how risk management can prevent environmental damage generated in adjacent properties, as well as the need to adapt to the legislation in order to avoid damage to the business and the environment. The methodology has a bibliographical and documental base, of exploratory character, with research in books, periodicals, articles, academic publications, theses, dissertations, legislation and jurisprudence. As a result of the research, attached to the dissertation, a risk management manual is presented with measures to be adopted to minimize the environmental impacts caused by the use of agrochemicals, hoping to contribute to the protection of the environment.
Keywords: Responsabilidade civil; Agronegócio; Agrotóxico; Danos ambientais; Meio ambiente; Civil responsibility; Agribusiness; Pesticides; Environmental damage; ACCNPQ::Ciências Sociais Aplicadas::Direito